Brazilian Literature: Contemporary Urban Fiction - William Foster, David (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
Thanks to additional funding from the NEH, the period from the end of the seminar to the end of the grant period has been used to enhance that site. Participants were asked to provide input, and their suggestions have been taken into account. The enhanced website includes relevant material generated by the seminar, in addition to collateral material that has been subsequently identified. It also includes a couple of Work in Progress sites that will have material posted to them as it is assembled. For example, we are in the process of preparing a registry of contemporary Brazilian filmmaking, something too vast to complete before the end of the grant period. Additionally, we have opened two categories to which material will be added as we receive it. One is devoted to course syllabi and the other to work in progress. In the latter category, seminar participants, as well as members of the Brazilian studies community at large, will be able to post preliminary versions, abstracts, grant applications of work in progress. This will not be a totally unrestricted site, as all potential submission will be vetted by the Director and, when necessary, by members of the Brazilian studies community. The intent is not to impose the sort of academic rigor of a scholarly journal. Rather, it is to ensure some level of academic relevance and professional format. An announcement of these two categories will be posted to the listserv of the Brazilian American Studies Association. The goal is to keep this website open indefinitely and to add material as it becomes available, toward providing an important site for information regarding Brazilian cultural studies.